When Context Matters: Variations in Classroom Management Effectiveness Across Learning Contexts in an Indonesian Islamic Secondary School - Naila Salwa Salsabila; Sadam Fajar Shodiq (Kuras Institute, 2025)
Purpose − Classroom management is a key factor influencing the quality of learning, student engagement, and academic achievement. However, the effectiveness of classroom management is not always universal, as it is influenced by the various learning contexts teachers face. This study aims to analyze variations in the effectiveness of classroom management across different learning contexts at an Islamic secondary school in Indonesia. Method − The study employs a qualitative approach with a case study design. Data were collected through non-participant direct observation of four classes in different Islamic Religious Education subjects, namely Fiqh, Tarikh, the Qur’an and Hadith, and Arabic. Data was analyzed using thematic analysis. The results indicate that the effectiveness of classroom management varies significantly across learning contexts. Classes with high levels of effectiveness were characterized by active teacher–student interaction, high student engagement, and adaptive management strategies. Conversely, lower effectiveness was found in learning contexts influenced by student fatigue, low participation, and limited interaction during the learning process. Findings − The study’s findings also indicate that class duration, class size, physical classroom conditions, subject characteristics, and the quality of teacher–student relationships are contextual factors influencing the effectiveness of classroom management. This study confirms that the success of classroom management is determined not only by the application of specific strategies but also by the teacher’s ability to adapt those strategies to the learning conditions at hand. These findings enrich the literature on contextual classroom management and provide practical implications for the development of teacher competencies in Islamic secondary schools.